Individual ambient ware potato storage excels in Uganda. Research Brief 06 - Wauters, P.; Parker, M.; Naziri, D. (International Potato Center, 2020)
Improved individual ambient storage units allow proper ware potato storage, are easy to maintain and help smallholder farmers fetch higher prices; more education and suitable financial products are needed that entice farmers to invest in these units to enable greater profitability.